Relação entre a espessura médio-intimal das artérias carótidas e as apresentações da doença hepática gordurosa não-alcoólica: esteatose não-alcoólica e esteatohepatite - Ana Cristina Lopes Albricker (2013)
Introduction: non-alcoholic fatty liver disease (NAFLD) is a major cause of chronic liver disease in the West. It encompasses a spectrum of clinical and pathological conditions ranging from non-alcoholic steatosis (NAS) and nonalcoholic steatohepatitis (NASH) to liver fibrosis/cirrhosis. It is frequently associated with metabolic syndrome (MS) and the majorcause of death in patients with NAFLD is coronary artery disease. Increased intima-media thickness (IMT) of the carotid arteries is a marker of subclinical cardiovascular disease and seems to be an indicator of NAFLD severity. The aim of this study was to investigate the association between carotid IMT measured by radiofrequency and the clinical forms of NAFLD: NAS and NASH. Methods: 34 adult patients with NAS and 20 with NASH were investigated. The two groups clinical and metabolic characteristics and carotid artery IMT measured by radiofrequency were compared. IMT values of the NAFLD patients were also compared to those of 26 asymptomatic controls, without MS and/or NAFLD. Results: insulin resistance including cases of diabetes mellitus, and high canalicular liver enzyme serum levels were more frequent in the NASH group. Except for the right internal carotid artery IMT measurement and the combined measurement of the right side (common carotid artery, carotid bifurcation and internal carotid) that were higher in the NAS group, there were no other significant differences between the groups. However, the NASH groups cardiovascular risk tended to be higher according to the Framingham score. Conclusion: no clinically significant association was found between carotid IMT radiofrequency measurements and NAFLD clinical forms: NAS and NASH. IMT of the NAFLD patients was also similar to that of the control group. IMT differences observed between the NAS and NASH groups seem to be related to chance or sample limitations. Thus, they should be interpreted with some caution.